Reduced Air Leakage During Non-Invasive Ventilation Using a Simple Anesthetic Mask With 3D-Printed Adaptor in an Anthropometric Based Pediatric Head–Lung Model - Hovenier, Renée; Goto, Lyè; Huysmans, Toon; van Gestel, Monica; Klein-Blommert, Rozalinde; Markhorst, Dick; Dijkman, Coen; Bem, Reinout A. (Frontiers in Pediatrics, 2022)
Non-invasive ventilation (NIV) is increasingly used in the support of acute respiratory failure in critically-ill children admitted to the pediatric intensive care unit (PICU). One of the major challenges in pediatric NIV is finding an optimal fitting mask that limits air leakage, in particular for young children and those with specific facial features. Here, we describe the development of a pediatric head-lung model, based on 3D anthropometric data, to simulate pediatric NIV in a 1-year old child, which can serve as a tool to investigate the effectiveness of NIV masks. Using this model, the primary aim of this study was to determine the extent of air leakage during NIV with our recently described simple anesthetic mask with 3D-printed quick-release adaptor, as compared to a commercially available pediatric NIV mask. The simple anesthetic mask provided a better seal resulting in lower air leakage at various positive pressure levels as compared to the commercial mask. These data further support the use of the simple anesthetic mask as a reasonable alternative during pediatric NIV in the acute setting. Moreover, the pediatric head-lung model provides for a promising tool to study the applicability and effectiveness of customized pediatric NIV masks in the future.